Transportation in an Age-Diverse Society. (September 2014) - Lewis, Bridget A.; Baldwin, Carryl L.; Chrysler, Susan T.; Foley, James P.; Hancock, Peter A.; Klauer, Sheila G.
In our rapidly diversifying society the needs of sometimes vastly different populations must be considered. The current population is made up of a greater number of older adults, "Baby Boomers" and younger adults "Millenials" than the current middle aged-adult population. These two generations have consistently forced change on many fronts, and will continue to do so, particularly in the area of transportation. This panel is intended to address transportation research and design needs in our ever-diversifying society, from driver-interface (DVI) design to public transportation needs, from increased safety systems to the integration of technology for our navigation of various forms of transportation. Specifically, needs that might require researchers to consider the design of systems to address the sometimes conflicting abilities, desires, cultural and demographic factors, and personal goals related to age groups separated by anywhere from 20 to 60 years in age. Panelists included have a broad range of expertise working with technology, transportation, and both older and younger adult population groups.